PEMBELAJARAN TARI KREASI LAMPUNG MELALUI KOREOGRAFI DI SMAN 5 BANDAR LAMPUNG - Nabilla Kurnia Adzan; Wini Tarmini; Fitri Daryanti (Jurnal Seni dan Pembelajaran, 2014)
This research aims to describe the process to learning results of Lampung creation dance using a choreography approach. This research uses descriptive qualitative approach. This research instrument uses student and teacher activities sheets, and practice tests. Research result shows that in the learning process all of students has understand the concept of dance creation learning using choreography approach through the audio visual phase, exploration, and improvisation, this also can be seen in the process of choreography approaches that include some aspects, that is exploration phase has an average value of 75 with a good criteria and improvisation phase has an average value of 85 with an excellent criteria. Students learning result show a good creativity because with choreography, students looks easier to create a new creation dance. It can be seen by students practice test, has anaverage value 67,83 with a good criteria.Penelitian ini bertujuan untuk mendeskripsikan proses hingga hasil pembelajaran tari kreasi Lampung melalui koreografi. Penelitian ini menggunakan metode deskriptif kualitatif. Instrument penelitian menggunakan panduan aktivitas siswa, aktivitas guru dan tes praktik. Hasil penelitian menunjukan pada proses pembelajaran siswa telah memahami konsep pembelajaran tari kreasi melalui koreografi berdasarkan tahapan audio visual, eksplorasiasi dan improvisasi hal ini dapat dilihat juga dengan penilaian aktivitas siswa pada proses pembelajarandengan rata-rata nilai siswa 80 mendapatkan kriteria baik sekali. Hasil belajar siswa menunjukan tingkat kreativitas yang baik dikarenakan dengan koreografi siswa lebih mudah menciptakan gerak tari kreasi hal ini dibuktikan dengan nilai tes praktik siswa mendapatkan rata-rata nilai 67,83 dengan kriteria baik.Kata kunci : koreografi, pembelajaran, tari kreasi.